2016
DOI: 10.18632/oncotarget.10931
|View full text |Cite
|
Sign up to set email alerts
|

Functional intratumoral lymphatics in patient-derived xenograft models of squamous cell carcinoma of the uterine cervix: implications for lymph node metastasis

Abstract: Studies of cell line-derived human tumor xenografts have suggested that the lymphatics seen in immunohistochemical preparations from non-peripheral regions of tumors are nonfunctional. In this investigation, lymphangiogenesis, hemangiogenesis, and lymph node metastasis were studied in patient-derived xenograft (PDX) models of carcinoma of the uterine cervix. Lymph vessel density (LVD) and blood vessel density (BVD) were measured in immunohistochemical preparations. The expression of angiogenesis-related genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…In our analysis, N1 stage was a significant factor that was associated with LVI in type IV HC patients. It is generally known that tumor cells and tumor stromal cells (such as macrophages and thrombocytes) can produce pro-lymphangiogenic factors, which increase lymphovascular density in and around the tumors[ 27 , 28 ], mainly peritumoral regions. Lymph node metastases often occurred in tumors lacking intratumoral functional lymphatics, suggesting that functional lymphatics at the peritumoral regions are the route of lymphatic dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, N1 stage was a significant factor that was associated with LVI in type IV HC patients. It is generally known that tumor cells and tumor stromal cells (such as macrophages and thrombocytes) can produce pro-lymphangiogenic factors, which increase lymphovascular density in and around the tumors[ 27 , 28 ], mainly peritumoral regions. Lymph node metastases often occurred in tumors lacking intratumoral functional lymphatics, suggesting that functional lymphatics at the peritumoral regions are the route of lymphatic dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has developed a panel of four PDX models of squamous cell carcinoma of the uterine cervix, differing in molecular and biological properties. Despite being intramuscular and thus ectopic tumor models, previous validation of the BK-12, ED-15, HL-16, and LA-19 tumors has confirmed that essential features of the donor patients’ tumors are retained after xenotransplantation [ 18 , 19 ]. Furthermore, the highly different MVDs, IFPs, and fractions of hypoxic tissue found among these tumor xenografts make them suitable models for evaluating the hypothesis of investigation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Adult (8–12 weeks of age) female BALB/c nu / nu mice were used as host animals for xenografted tumors. Four PDX models (BK-12, ED-15, HL-16, and LA-19) of squamous cell carcinoma of the uterine cervix, obtained from patients with FIGO stage IIB disease prior to treatment, were included in the study [ 18 , 19 ]. We have established two frozen cell stocks of these models, one from xenografted tumors in passage 2 ( early generation) and the other from xenografted tumors transplanted serially in mice for approximately 2 years ( late generation).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, studies of melanoma and cervix carcinoma xenografts without intratumoral lymphatics have revealed that lymph node metastasis is associated with high IFP, both in tumors with and tumors without hypoxic regions [ 41 , 42 ]. However, some patient-derived xenograft models of cervix carcinoma can develop functional intratumoral lymphatics, and functional intratumoral lymphatics may promote lymph node metastasis and reduce tumor IFP, leading to an inverse relationship between IFP and metastatic propensity [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative studies were carried out on preparations cut through the central regions of tumors, and three sections of each staining were analyzed for each tumor. Blood vessel density was scored by counting CD31-positive vessels in whole tumor cross-sections as described elsewhere [ 54 ]. The density of peritumoral lymphatics was assessed by counting LYVE-1-positive vessels in the muscle tissue located within a distance of 0.5 mm from the tumor surface.…”
Section: Methodsmentioning
confidence: 99%